The Influence of Financial Literacy, Self-Control, and the Social Environment on Consumptive Behavior in Urban Communities in the Banyumas Regency Area - Gunata, Margareta; Syaifudin, Noor; Hendrian, Hendrian (Syntax Corporation, 2024)
The main aim of this research is to see the influence of financial literacy, self-control, and social environment on consumptive behavior in urban communities in the Banyumas Regency area. This research was conducted with a quantitative approach. The population in this research is urban communities in the Banyumas Regency area with a sample size of 117 respondents. The collected data will be analyzed using descriptive analysis, correlation, and multiple regression with the help of SPSS software. The results of the analysis show that there is a real influence of financial literacy and self-control on consumptive behavior in urban communities in the Banyumas Regency area. There needs to be awareness of the importance of self-control and a positive social environment in urban communities in the Banyumas Regency area so that they do not engage in excessive consumptive behavior. Apart from that, people must also continue to hone their knowledge and understanding of the concept of risk in finance, skills, motivation, and self-confidence to be able to make effective decisions regarding financial issues. This research was conducted based on empirical phenomena in the field regarding consumptive behavior that often affects the lives of urban communities, especially communities in the Banyumas Regency, which has not been studied previously.